Information Communication Technology (ICT)-Based Instructional Software and Its Effectiveness in Teaching High School Geometry - Ramil M. Arciosa (Universitas Pendidikan Indonesia, 2022)
The study aimed at developing and testing an ICT-based instructional software called UBDGEOMESYS, to facilitate students' learning of selected topics in Mathematics. It is a researcher-created program that uses a language known as Microsoft Visual Basic. The respondents of the study included 2 groups of second-year Special class students of Koronadal National Comprehensive High School (KNCHS). Data for analyses were the scores from tests administered before and after the instruction. Validity and reliability activities were done to ensure the quality of the tool. The evaluation showed that the ICT-based material was of good quality along with its content, technical and instructional value. The analysis also indicated that the learning achievement of students exposed to the instructional software (R2 = 0.284) was reasonably higher than those who utilized the traditional way (R2=0.05).